Increasing Legal Capacity for Communities in the Context of Realizing a Village of Law Awareness and Child Friendly - Prayogo, Bagus Edi; Amanah, Amanah; Pradana, Tirta Mulya Wira; Rodiyah, Rodiyah (Indonesian Journal of Advocacy and Legal Services, 2019)
The purposes of community services program and research are to support, analyze, and create an accountable, transparent, independent, legally-aware and child-friendly village in Kedungkelor village, Warureja sub-district, Tegal regency. The paper analyzed two major parts are taken in the title of the service as well as aware of the law and child worth. Legal awareness and worthy of children are considered important because the child's world is very determining how the child will grow up later so that the village apparatus and the community need to increase of awareness related to the law and in the policies formulated by the village government or the community itself must be child-oriented. The program implemented a to realize a village that is aware of the law and suitable for children in our service is providing free legal assistance, door-to-door programs for families aware of the law and the environment, leadership training, healthy snacks and hand hygiene programs, and anti-bullying programs. The paper concluded that there are some forms of activity that will initiate the formation of a village that is aware of the law and is suitable for children.